ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (Studi Empiris Pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia) - Ravika Permata Hati; Sri Mulyati; Paza Kholila (EQUILIBIRIA, 2019)
High target State Budget (APBN) of the Taxes sector set by the government, prompting the company to undertake tax management. Many of the companies who want to suppress the tax obligations causes the difference between the calculation of the tax burden on the rates set by the law and reported in the financial statements. Several factors can be maximized by the company for the tax management activities include company size, leverage, profitability, and the intensity of the of fixed assets.The population in this study all manufacturing companies food and beverage subsector listed on the Stock Exchange in 2013 - 2017. The sample in this study is the most companies listed on the Stock Exchange in 2013-2017 with a sampling technique is purposive sampling and obtained a sample of 12 companies. Type of data is secondary.Methods of data collection using documentation. The analysis technique used is multiple regression.Results of analysis using multiple regression showed that: (1). Company size is not a significant effect on the Tax Management. (2). Leverage significant effect on the Tax Management. (3). Profitability is not a significant effect on the Tax Management. (4) The intensity of Fixed Assets significant effect on the Tax Management.  Keywords: Tax Management, Company Size, Leverage, Profitability, and Intensity Fixed Assets.